Access-Based Services as Substitutes for Material Possessions: The Role of Psychological Ownership. (August 2020) - Fritze, Martin P.; Marchand, André; Eisingerich, Andreas B.; Benkenstein, Martin
Access-based services (ABS)—in which consumers do not physically own material goods but gain access to services by registering with the provider—have risen in popularity as an alternative to individual ownership and conventional consumption. Yet companies still face key challenges in promoting these services. Prior research indicates that consumers assign significant importance to their material possessions; the current study investigates how psychological ownership, the mental state of perceiving something as one's own, attained through ABS might lead customers to increase their service use and forgo material ownership. With four studies, using cross-sectional, longitudinal, and experimental data, as well as combined self-reports with usage data, we theorize and demonstrate this effect. Firms that offer ABS can increase customers' service psychological ownership, which acts as a psychological substitute for physical ownership and increases ABS use. The results suggest ways managers can leverage the psychological power of ownership feelings, rather than try to fight the lack of actual ownership, in access-based consumption contexts.